At the dawn of history: ancient Near Eastern studies in honour of J. N. Postgate - Heffron, Yaǧmur; Stone, Adam; Worthington, Martin (Eisenbrauns, 2016)
Contents -- Editors' Preface -- Nicholas Postgate's Publications -- A Fragment of a Stele from Umma -- In the Shade of the Assyrian Orchards . . . -- The Šu-Suen Year 9 sa2-du11 ku5-ra2Flour Dossier from Puzriš-Dagan -- To Eat Like a God: Religion and Economy in Old Babylonian Nippur -- Remarks on the Earliest History of Horoscopy -- A Ceramic Assemblage of theEarly Literate Periods from Sumer -- Stolen, Not Given? -- Are We Any Closer to Establishing How Many Sumerians per Hectare?Recent Approaches to Understanding the Spatial Dynamics of Populations in Ancient Mesopotamian Cities -- New Perspectives on 'Early Mesopotamia' -- Of Arches, Vaults and Domes -- Ethnicity in the Assyrian Empire: A View from the Nisbe, (III): "Arameans" and Related Tribalists -- Instruktionen Tukultī-Ninurtas I. -- Gods, Temples, and Cult at the Serviceof the Early Hittite State -- The Ending of the Çineköy Inscription -- A New Palatial Ware or a Case of Imitation of Egyptian Pottery? The Brownish Red Slip (BRS) from Qatna and Its Significance within the Northern Levantine Ceramic Tradition of the Mid-Second Millennium BC -- Building on the Past: Gertrude Bell and the Transformation of Space in the Karadağ -- Studies in the Lexicon of Neo-Aramaic -- The Temple of Salmānu at Dūr-Katlimmu, Nergal of Hubšalum, and Nergal-ereš -- Between Slavery and Freedom -- The King and His Army -- Two Middle Assyrian Delivery Notes fromthe British Museum's Tablet Collection -- The Governors of Halzi-atbariin the Neo-Assyrian Period -- Never the Same River Twice: The Göksu Valley Through the Ages -- Piecing the Jigsaw . . . -- A Palace for the King of Ereš? Evidence from the Early Dynastic City of Abu Salabikh, South Iraq -- How Many Sumerians DoesIt Take to Put Out the Rubbish? -- The Location of Raṣappa -- Making Fire in Uruk-Period Abu Salabikh
Keywords: Festschrift; Geschichte; Mesopotamien; Alter Orient